Are Capital Market Anomalies Common to Equity and Corporate Bond Markets? An Empirical Investigation. (15th August 2017) - Chordia, Tarun; Goyal, Amit; Nozawa, Yoshio; Subrahmanyam, Avanidhar; Tong, Qing
Abstract : Corporate bond returns exhibit predictability in a manner consistent with efficient pricing. Many equity characteristics, such as accruals, standardized unexpected earnings, and idiosyncratic volatility, do not impact bond returns. Profitability and asset growth are negatively related to corporate bond returns. Because firms that are profitable or have high asset growth (and hence more collateral) should be less risky, with lower required returns, the evidence accords with the risk–reward paradigm. Past equity returns are positively related to bond returns, indicating that equities lead bonds. Cross-sectional bond return predictors generally do not provide materially high Sharpe ratios after accounting for trading costs.